2001
DOI: 10.1007/s007010170015
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Experience of 120 Patients with Lumbosacral Lipomas

Abstract: The surgical experience of 120 patients with lumbosacral lipomas is described. 47 of 120 patients were preoperatively found to be neurologically intact, the remaining 73 patients presented with various neurological signs including reflex changes, sensory disturbances, muscle weakness and sphincter problems. Neuro-imagings allowed a classification of lumbosacral lipomas into five types: (1) dorsal type; (2) caudal type; (3) combined type; (4) filar type; and (5) lipomyelomeningocele. Although all 120 patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 13 publications
0
79
0
Order By: Relevance
“…Other studies have shown that minimally invasive open microscopic approaches with tubular and expandable retractors are sufficient to achieve the same goals as traditional open approaches (6,7). Surgical approaches for treating lipomyelomeningocele face significant risks for scar formation, nerve damage and spinal fluid leakage (4,5). The morphology of the lipomyelomeningocele in this case leant itself to a minimally invasive treatment because the lipoma tethered the cord to the filum instead of to the spinal cord.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies have shown that minimally invasive open microscopic approaches with tubular and expandable retractors are sufficient to achieve the same goals as traditional open approaches (6,7). Surgical approaches for treating lipomyelomeningocele face significant risks for scar formation, nerve damage and spinal fluid leakage (4,5). The morphology of the lipomyelomeningocele in this case leant itself to a minimally invasive treatment because the lipoma tethered the cord to the filum instead of to the spinal cord.…”
Section: Discussionmentioning
confidence: 90%
“…The standard surgical approach is to partially resect the lipoma down to its neural attachment, section the filum terminale, and create a dural expansion graft to prevent future tethering. The complications inherent to this approach include spinal fluid leak, nerve damage, worsened bowel and bladder dysfunction, and re-tethering (4,5). Here we describe a minimally invasive endoscopic-assisted approach to untethering the spinal cord that illustrates several technical advantages to utilizing endoscopic visualization in cord untethering.…”
Section: Introductionmentioning
confidence: 99%
“…28 Surgically orientated classification of spinal lipoma was first proposed by Chapman and underwent various modifications based on MRI findings. 1,2,8,16,18 Chapman's classification is still useful today but does not account for spinal lipomas originating from failed secondary neurulation. Some have included the filum lipoma in the classification.…”
mentioning
confidence: 99%
“…Some have included the filum lipoma in the classification. 1 However, because this classification is simply based on the site and morphology of the spinal lipoma, it is now considered to have less clinical significance.…”
mentioning
confidence: 99%
“…Lipomas of conus medullaris are further classified according to Chapman [6] into dorsal, caudal, and transitional lipomas. Intraspinal lipomas are most commonly found in the lumbosacral area (90%) [1,17,23,26]. Excluding the lumbosacral spine, the reported distribution of lipoma was thoracic in 32% of cases, cervicothoracic in 24%, and cervical in 13% [18].…”
Section: Discussionmentioning
confidence: 99%